PENGARUH MOTIVASI TERHADAP KINERJA PETUGAS RESCUER PADA KANTOR PENCARIAN DAN PERTOLONGAN KELAS B PALU - Arifuddin Arifuddin; Abu Tjaiya; Mustainah Mustainah (Katalogis, 2018)
The purpose of this study is to determine the effect of motivation on the performance Officer Rescuer On The Search And Rescue Office Class B Palu and to find out how much influence motivation on the performance of Rescuer Officers On The Search And Rescue Office Class B Palu. This study uses the type of research associative, with the number of samples or respondents who were involved as many as 63 people respondents with a total sampling technique. In addition, in the techniques of data collection in this study through observation, distribution of questionnaires, interviews and documentation. By method of data analysis through descriptive analysis of percentage and simple linear regression. From the results of research researchers note that the motivation has a positive influence on the performance of officers rescuer On The Search And Rescue Office Class B Palu. In addition, the magnitude of the influence of motivation on the performance of officers rescuer Office of Search and Rescue seen from the value of coefficient of determination (R2) of 0.334, which coefficient value is located at the interval of 0.200-0.399, so included in the low category.